Understanding Chinese Luxury Fashion Goods Consumption in Present Day China - Webber, K.S. (2010)
The global luxury goods market has grown considerably in the past few decades and continues to do so. However, research literature on the topic, especially on Eastern cultures, is still limited. This study sets out to understand luxury goods consumption in Chinese culture. Ten Chinese students were interviewed to gauge an understanding of how perceptions of ‘luxury’ and what motivates them to purchase it.